A quinoline alkaloid potentially modulates the amyloidogenic structural transitions of the biofilm scaffolding small basic protein. Issue 4 (4th March 2023) - Admane, Nikita; Kothandan, Ram; Syed, Sowfia; Biswas, Sumit
Abstract: Bacterial biofilm formation by communities of opportunistic bacterial pathogens like Staphylococcus epidermidis is regarded as the primary virulence mechanism facilitating the spread of detrimental nosocomial and implant-associated infections. An 18-kDa small basic protein (Sbp) and its amyloid fibrils account for strengthening the biofilm architecture and scaffolding the S. epidermidis biofilm matrix. Our study reports systematic analysis of the amyloidogenic structural transitions of Sbp and predicts the amyloid core of the protein which may trigger misfolding and aggregation. Herein, we report the novel amyloid inhibitory potential of Camptothecin, a quinoline alkaloid which binds stably to Sbp monomers and redirects the formation of unstructured regions further destabilizing the protein. Molecular dynamics simulations reveal that Camptothecin averts β-sheet transitions, interrupts with electrostatic interactions and disrupts the intermolecular hydrophobic associations between the exposed hydrophobic amyloidogenic regions of Sbp. Collectively, our study puts forward the first report detailing the heteromolecular associations and amyloid modulatory effects of Camptothecin which may serve as a structural scaffold for the tailored designing of novel drugs targeting the S. epidermidis biofilm matrix. Communicated by Ramaswamy H. Sarma